Problems and Challenges in Designing ESP Course for Hospitality and Tourism Students of STP Mataram - Ida Nyoman Tri Darma Putra; Ulfan Mulyawan (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
The objective of this study is to identify the difficulties and obstacles that instructors encounter when designing ESP English course for tourism students. Communication with foreigners was deemed by the majority of Lombok's stakeholders to be the most formidable challenge to the local community. Students have to be able to speak and write English because of how quickly knowledge and information spreads in this globalized world. To accommodate the requirements of students, English for Specific Purposes (ESP) is structured. In this study, the ESP lecturers at STP Mataram are degrees in education and/or language; hence, it is doubtful that they have specific understanding of the subjects that the students are studying. It could be challenging for the lecturers at STP Mataram to manage and design course with relevant activities in the classroom, much less respond to questions about subjects, technical terms, and ideas that they don't fully understand. Not only do lecturers face difficulties in creating materials in realistic forms, but they also face difficulties in choosing texts or other resources based on their own degree of expertise in the subject. In teaching the class efficiently, ESP lecturers must also develop the syllabus, supply the necessary materials, work with subject/content specialists, carry out research, and assess the students and the course. A thorough need analysis will enable the course designer to create a unique, appropriate course for the students and consider the students' prior knowledge of how to use English language.